Identifikasi Gaya Belajar Siswa Dengan Metode Backward Chaining - Miftahul Mardiyah (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2025)
Teaching and learning activities are one of the efforts to improve the quality of formal education. Every student has their own uniqueness, including in learning. There are 3 types of learning styles, including Visual, Auditory, and Kinesthetic. All three have unique characteristics, and the application of the Backward Chaining method in this study is quite influential because it has the same results as manual calculations.